WHAT DRIVES CONSUMER SATISFACTION IN USING ISLAMIC FINANCIAL TECHNOLOGY? - Utami, Cahyaning Budi; Slamet, Slamet (UNISSULA, 2021)
The purpose of this study is to examine the relationship between attitude toward Islamic financial technology as specific religious attitude and consumer based brand equity as market driven variable toward consumer satisfaction in Islamic financial technology. A questionnaire was designed to collect data from users of online service of Islamic financial technology in Indonesia. Incidental sampling method was adopted to collect data from the existing users. Regression analysis was used to test the proposed research model. This study become the first research how specific religious attitudes and market driven affect the consumer satisfaction. This research is a survey-based study. Hence a representative sample is mandatory. The result show that attitude toward Islamic financial technology insignificantly influences consumer satisfaction, meanwhile the consumer based brand equity has a positive effect on consumer satisfaction.